Manuk Nom As A Java-Netherland Acculturation Form Of The Government Culibary Sultan HB VII-VIII (1877-1939) - Septarina, Sri Wahyuning (Institut Seni Indonesia Denpasar, 2019)
Manuk nom, one of the typical Karaton Yogyakarta desserts that has historical value that cannot be separated from the influence of acculturation of Javanese-Dutch culture. Nom manuk is made of green sticky rice tape and the egg is equipped with two melinjo chips placed on top of it resembling bird wings. During Sultan HB VII’s reign, Yogyakarta experienced a period of transition to modernity. During this period the life of the Yogyakarta Palace received elements of modern education, modern minds, ideas, enthusiasm, ideology and western culture. The purpose of this paper is to find out the history of the development of Javanese-Dutch acculturation in the form of culinary in the era of Sultan HB VII-VIII’s administration. The research method used is qualitative by means of collecting data in the form of observation, interviews, literature data and documentation. This study uses the acculturation theory of cultural approaches to history. The implication of Manuk Nom, which is a favorite food of the Sultanate of Yogyakarta Sultanate, is a reflection of Javanese people’s pride in the culinary results of Javanese-Dutch acculturation as a reflection of national identity.